2018
DOI: 10.5505/tjtes.2018.82357
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Cholecystitis During Pregnancy: A Single Center Experience

Abstract: BACKGROUND: This study aimed to present to evaluate the results of two different approaches in the management of acute cholecystitis during pregnancy: immediate surgery and delayed surgery following conservative management. METHODS: In this study, 20 pregnant women who were treated in our clinic for acute cholecystitis between 2010 and 2018 were included in the analysis. Demographic characteristics, parameters related with acute cholecystitis (gallbladder wall thickness, laboratory data), duration of hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…These findings are in line with our results showing that surgical intervention had no influence on pregnancy outcome. Barut et al and others have concluded that although conservative management of acute cholecystitis was favored, early surgical intervention showed better results [7]. Cholecystectomy was performed in our study in 4 cases (5%), without adverse effects on pregnancy.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…These findings are in line with our results showing that surgical intervention had no influence on pregnancy outcome. Barut et al and others have concluded that although conservative management of acute cholecystitis was favored, early surgical intervention showed better results [7]. Cholecystectomy was performed in our study in 4 cases (5%), without adverse effects on pregnancy.…”
Section: Discussionmentioning
confidence: 53%
“…The most frequent indications for surgery during pregnancy are infections such as acute appendicitis and cholecystitis [5][6][7][8][9][10][11][12][13][14]; pregnant women may also require acute surgical intervention for ovarian disorders and bowel obstruction, as well as for traumatological or oncological indications [11]. Any kind of pathology can occur in pregnant women and require immediate surgical treatment and optimized interdisciplinary management to achieve maximum safety for both mother and fetus, to avoid teratogenous medication, fetal acidosis and hypoxemia, and adverse pregnancy outcomes such as miscarriage, stillbirth or premature birth [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Study on surgical resection for GBC has revealed GGT’s diagnostic value[ 16 ]. Clinically, GGT has been administered in the evaluation of gallbladder diseases such as cholangiocarcinoma[ 17 ], biliary atresia[ 18 ], and cholecystitis[ 19 ]. Emerging evidence also indicates that higher GGT levels may be linked to a high cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…1 3.5-10% of all pregnant women have USG detectable cholelithiasis, however, only 0.05-0.3% will develop cholecystitis. [2][3][4] Common symptoms of acute cholecystitis include severe pain in the RUQ or epigastrium, which can radiate to the right shoulder or back, and there is often fever, nausea, vomiting and anorexia. As these symptoms are not very specific and the pain localization is often unclear, cholecystitis can be difficult to recognize in pregnant women, and there are many differential diagnoses to be considered, including acute pyelonephritis, fatty liver disease and intrahepatic cholestasis of pregnancy, which were the first suspected diagnoses in our case.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 If such symptoms are present, the best diagnostic method for differentiation is abdominal USG, which is very reliable with an accuracy of 95-98% in detecting gallstones, however, it can be technically challenging and requires a professional, therefore in this case the patient was sent to a multidisciplinary hospital where such professionals were available. 4,7 ERCP is also a common diagnostic method of choice as it provides therapy options as well, however, in this case MRI was chosen to evaluate the dynamics of the condition. 4,8 According to many studies and guidelines, laparoscopic cholecystectomy is the method of choice in the management of acute cholecystitis in pregnant patients.…”
Section: Discussionmentioning
confidence: 99%